Aspek Sosial Ekonomi dan Potensi Agribisnis Bunga Krisan di Kabupaten Pasuruan JawaTimur - Al Gamal Pratomo; Kuntoro Boga Andri (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTRecently, chrysant emum agribu s siness has grown rapidly in the central pro duction of ornamental plant in East Java. One of the areas is in Tutur Sub District, Pasuran District , located in a mountainous area with an altitude of 800 mabove sea level. The study was aimed to collect information and analyse of the socio economic aspects and potency of the chrysant emum agribus s iness in Pasuruan, especially from Tutur Sub District. The research was conducted during August to December 2009, using the Focus Group Discussion (FGD), field survey, questionairy and secondary data collection from farmers, entrepreneurs, and others stakeholders in the area. The study illustrated the enormous economic potential of this commodity in the studied area. Its great potency, need s to be followed by improvement in farming systems, institutional management, marketing and general bu s siness management. So far chrysant emum product marketing rely on local markets. Technically, the studied area is suitable for cultivation because of the appropriate agroecology condition. From the economic and social point of view, the development of this sector is very useful for the community and regional economy, as many job , and business opportunities developed . This study showed chrysant emum farming financially benefited, where in one growing season it provides profitability (ROI) 70% of the invested funds. The added value alon g the market chain also show a proper profit and fair to the businesses players (farmers and traders).Keywords: chrysant, ornamental plants agribusiness, Pasuruan, value chain analysisABSTRAKAgribisnis krisan tumbuh pesat beberapa tahun terakhir di sentra produksi tanaman hias Jawa Timur, salah satunya di Kecamatan Tutur, Kabupaten Pasuruan. Kawasan ini terletak di daerah pegunungan dengan ketinggian di atas 800 m di atas permukaan laut . Penelitian bertu juan mendapatkan informasi dan meng analis is aspek sosial ekonomi dan potensiagribisnis krisan di Kabupaten Pasuruan, khususnya Kecamatan Tutur yang merupakan wilayah sentra pengembangan. Penelitian dilakukan Agustus sampai Desember 2009 menggunakan metode Focus Group Discussion ( FGD ), surveilapang, kuesioner dan pengumpulan data s e kunder dari para petani, pelaku usaha, serta stakeholder lainnya. Hasil penelitian menggambarkan potensi ekonomi yang besar agribisnis ini. Potensi besar tersebu t, perlu diikut i perbaikan siste m budidaya, manajemen kelembagaan, pemasaran dan pengelolaan bisnis secara umum. Sejauh ini pemasaran bunga krisan masih mengandalkan pasar lokal. Secara teknis, lokasi sentra Kecamatan Tutur sesuai untuk pengembangan budidaya krisan karen a agroekologi yang sesuai. Dari aspek ekonomi dan sosial, pengembangan agribisnis bunga ini sangat bermanfaat bagi masyarakat dan perekonomian daerah, karena membuka kesempatan kerja dan berusaha. Penelitian menunjukkan bahwa secara finansial usahatani krisan memberikan keuntungan, yaitu dalam satu musim tanam memberikan profitabilitas (ROI) 70% dari dana yang diinvestasikan. Nilai tambah sepanjang rantai pemasaran memperlihatkan keuntungan yang layak dan adil bagi para pelaku usaha (petani dan pedagang ).Kata kunci: agribisnis tanaman hias, analisis rantai nilai, bunga krisan, Pasuruan